한국형 측정도구를 활용한 일부 노인의 구강노쇠와 노쇠의 관련성 - 한지형; Ji-hyoung Han; 황지민; Ji-min Hwang (Han'guk Ch'iwisaeng Hakhoe chi, 2025)
Objectives: This study aimed to assess the degree of oral aging and frailty and examine the relationship between them, thereby contributing to the search for effective strategies that highlight the importance of frailty and its prevention. Methods: This study was conducted with adults aged 65 years and older living in Seoul and the metropolitan area. Data were collected using a Korean-style measurement tool, a self-administered questionnaire, and interviews. The final analysis included 143 people. Results: Assessment of oral aging risk by general characteristics showed statistically significant association with age (p<0.01) and presence of chronic diseases (p<0.05). Evaluation of aging stage based on general characteristics also showed significant differences in age (p<0.05) and chronic disease status (p<0.05). A positive correlation was found between oral aging and aging, with a correlation coefficient of 0.603, indicating a statistically significant correlation (p<0.001). Conclusions: These findings demonstrate a close relationship between the two factors. This study confirmed that promoting oral health is an important factor in preventing frailty and suggests that policy efforts to support oral health in older adults should be further strengthened.